Production of Hydrogen Sulfide from D-Cysteine and Its Therapeutic Potential - Shibuya, Norihiro; Kimura, Hideo (Frontiers in Endocrinology, 2013)
Accumulating evidence shows that H2S has physiological functions in various tissues and organs. It includes regulation of neuronal activity, vascular tension, a release of insulin, and protection of the heart, kidney, and brain from ischemic insult. H2S is produced by enzymes from l-cysteine; cystathionine β-synthase, cystathionine γ-lyase, and 3-mercaptopyruvate sulfurtransferase (3MST) along with cysteine aminotransferase. We recently discovered an additional pathway for the production of H2S from d-cysteine. d-Amino acid oxidase provides 3-mercaptopyruvate for 3MST to produce H2S. d-Cysteine protects cerebellar neurons from oxidative stress and attenuates ischemia-reperfusion injury caused in the kidney more effectively than l-cysteine. This review focuses on a novel pathway for the production of H2S and its therapeutic application especially to the renal diseases.